Requirements of a Transport System User - Rudolf Kampf; Jan Lizbetin; Lenka Lizbetinova (Communications - Scientific letters of the University of Zilina, 2012)
This article deals with the problem of basic parameters which influence the selection of a mode of transport by a transport user. The article suggests the use of Saaty’s method as a method suitable for the determination of weights of importance of basic parameters (user’s requirements).